Relationship of Locus of Control with Academic Stress Student of SMA Negeri 7 Padang - Lismatusadiah Lismatusadiah; Marjohan Marjohan (Universitas Negeri Padang, 2021)
School can be a source of problems that ultimately cause stress to students. This problem arises due to the form of student difficulties in following and receiving lessons that lead to academic stress. The factors that influence academic stress are personality characteristics, one of which is locus of control. For this reason, this study aims to describe student academic stress, locus of control, and how the relationship between locus of control and student academic stress. This type of research is descriptive correlational with a population of 1,085 students. Sampling 292 students using the Slovin formula. The sampling technique used was stratified random sampling. The data collection instrument was a student academic stress questionnaire using a Likert scale and a locus of control inventory using standard techniques that had been adopted from Dr. Marjohan M.Pd., Kons. The data were processed using descriptive statistical analysis techniques and to test the data relationships were analyzed using the Pearson Product Moment formula with the program Statical Product and Service Solution (SPSS) version 20.0. The results of this study reveal that: (1) locus of control has an internal locus of control tendency, (2) students' academic stress is in the moderate category, (3) there is a significant positive relationship between locus of control and academic stress of students at SMA Negeri 7 Padang. with rtabel of 0.113 and rcount of 0.224 with a significant level of 0.000. So the better or the lower the student's locus of control score, the lower the academic stress. Based on the findings of this study, it is expected that the counseling teacher or counselor can provide assistance in the form of counseling guidance services.